2016
DOI: 10.1124/mol.116.103697
|View full text |Cite|
|
Sign up to set email alerts
|

All-Trans-Retinoic Acid Enhances Mitochondrial Function in Models of Human Liver

Abstract: All-trans-retinoic acid (atRA) is the active metabolite of vitamin A. The liver is the main storage organ of vitamin A, but activation of the retinoic acid receptors (RARs) in mouse liver and in human liver cell lines has also been shown. Although atRA treatment improves mitochondrial function in skeletal muscle in rodents, its role in modulating mitochondrial function in the liver is controversial, and little data are available regarding the human liver. The aim of this study was to determine whether atRA reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
1
22
1
Order By: Relevance
“…Overexpression of the atRAinducible RARb in mouse liver enhances fatty acid oxidation and energy expenditure (31), whereas the RARb2-specific agonist AC261066 reduces liver steatosis in HFD-fed mice (49). Increasing endogenous atRA concentrations by inhibiting the atRA-catabolic Cyp26 isozymes enhances expression of mitochondrial biogenesis markers Nrf1 and Pgc1b 5-to 10-fold (32). These data are consistent with atRA enhancing fatty acid oxidation and mitochondrial biogenesis in vivo and suggest processes contributing to the liver steatosis phenotype.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Overexpression of the atRAinducible RARb in mouse liver enhances fatty acid oxidation and energy expenditure (31), whereas the RARb2-specific agonist AC261066 reduces liver steatosis in HFD-fed mice (49). Increasing endogenous atRA concentrations by inhibiting the atRA-catabolic Cyp26 isozymes enhances expression of mitochondrial biogenesis markers Nrf1 and Pgc1b 5-to 10-fold (32). These data are consistent with atRA enhancing fatty acid oxidation and mitochondrial biogenesis in vivo and suggest processes contributing to the liver steatosis phenotype.…”
Section: Discussionsupporting
confidence: 54%
“…We undertook this research to reveal postnatal Rdh10 contributions to atRA function and to assess endogenous atRA actions. Previous studies focusing on specific organs or using vitamin A deficiency models revealed that atRA has widespread impact on metabolism, consistent with organ autonomous effects (15)(16)(17)20,(29)(30)(31)(32). Total Rdh10 ablation impairs the biogenesis of multiple organs, including the pancreas, and causes embryonic lethality between E10.5 and E13, but Rdh10 +/2 mice reportedly were "indistinguishable" from WT (33).…”
Section: Discussionmentioning
confidence: 56%
“…At 72 hrs, cells were harvested for mRNA analysis. CYP2D6 and SHP mRNA were quantified using q-RT-PCR (StepOnePlus ™ , Applied Biosystems, Carlsbad, CA) as previously described [27] using GAPDH as a housekeeping gene. Cells were harvested using Tri-reagent (Invitrogen, Grand Island, NY) and mRNA extracted according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…At 72 hrs, cells were harvested for protein analysis. Western blot analysis was done to measure CYP2D6 expression with β-actin as aloading control as previously described [27]. In brief, for western blotting, proteins from HepG2 cells were extracted as whole cell extract using whole cell lysis buffer in the presence of protease (Roche Applied Science, Indianapolis, IN) and phosphatase inhibitors (1 mM β-glycerol phosphate, 2.5 mM Na-pyrophosphate, 1 mM Na 3 VO 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation